Peningkatan Motivasi dan Prestasi Belajar Fiqh dengan Model Cooperative Learning Tipe Student Team Achievement Division pada Siswa Kelas IX A MTs Muhammadiyah Kasihan Bantul - Ma'ruf Yuniarno (Jurnal Pendidikan Madrasah, 2016)
Achievement of learning objectives can not be separated from the role of a teacher. Teachers should be a motivator for her students, so that their potential to be fully developed. Teachers should be able to create a classroom climate that is conducive to learning materials proposed for creative teacher will be able to manage the class that student achievement can be optimized. This study aims to determine how to improve students' motivation and achievement through cooperative learning model of STAD (Student Team Achievement Division). This research is a classroom action research. The subjects were students of class IX MTs Muhammadiyah Kasihan, Bantul in the academic year 2015/2016. The results of this study showed an increase learning motivation significantly. Percentage of students' motivation in pra-cycle by 26%, the first cycle of the first meeting by 30%, meeting II rose to 59%. Cycle II meeting I rose to 60% and then at a meeting II to 78%. Cycle III meeting I rose to 79% and on the meeting II rose to 85%. Student achievement obtained in the first cycle of the first meeting by 84.2%, meeting II rose to 88.1%. However, the second cycle of the first meeting fell to 85.1%, meeting II dropped significantly to 62.9%. Cycle III first meeting application STAD cooperative learning improved back to the percentage obtained rose to 97.8% and on the meeting II rose to 98.4%. The implementation of cooperative learning model of STAD can increase motivation and achievement by making modifications in the case; use of media interest, seating arrangements, and effective classroom management strategies.